Pattern of hematological malignancy in a tertiary level hospital in Kathmandu - Shrestha, Amar Narayan; Singh, Sunil Kumar; Deo, Rajiv Kumar; Joshi, Rinku; Poudel, Ayusha; Aryal, Barun Babu; Adhikari, Anurag (Journal of Pathology of Nepal, 2019)
Background: Hematological malignancies involve the blood elements, marrow, lymph and lymphatic elements and are among the common malignancies afflicting the human race. They tend to involve the extremes of the ages- the young and the elderly. Materials and Methods: A hospital register based retrospective study was conducted including the data of five years duration. The confirmation of diagnosis was done with blood smear examination, bone marrow examination and flow-cytometry. The epidemiological parameters were then calculated using Microsoft Excel and SPSS. Results: Among the total number of cases, 60.7% were males and 39.3% were females. Age group of 50 to 59 years was most commonly involved. Lymphoma (including Hodgkin’s and non-Hodgkin’s) was the most common hematological malignancy. Conclusions: Males are more afflicted by hematological malignancies and lymphoma was the commonest hematological malignancy.